منظور طلبة المرحلة المتوسطة للأنشطة اللغوية اللاّصفية واتجاهاتهم نحوها في ضوء بعض المتغيرات. - محمد سعيد محمد علي (Journal of College of Education, 2020)
Intermediate School Students’ Perception and Attitudes towards Extra-Curricular Language Activities in Light of some Variables The present research aimed at identifying the extra-curricular language activities that, suit the students of the intermediate school in Bisha, from their perception, and knowing their attitudes towards them. To fulfill this, the researcher designed an initial tool represented as a questionnaire consists of the most significant items, that can be included in the program of the extra-curricular language activities. Then he distributed it to a number of experts who were about (7) to ensure its reliability. In light of their corrections, it was developed to be valid for field data collection. To be sure of the reliability of its content, it was implemented on a pre-sample to know the co-relation between its dimensions by using Alfa Cronbach. The co-relation between the items ranged from (0.91 – 0.70). The reliability of the tool was (0.96), the reliability of the tool, indicates that, the tool has a high degree of stability and internal consistency between its statements, which gave an indication that, the results of the research are realistic, and can be generalized to the research community. The findings resulted in a number of indicators, some of which were: A list of non-classroom activities was reached which is suitable for intermediate school students in Bisha. Their attitudes towards the activities was positive. It resulted in a mean ranged from (2.27 – 2.12) which indicated the validity of the measuring tool. The attitudes of the students towards the teachers of Arabic, was positive: the mean was (2.25) and the standard deviation was (0.41). no co-relation of statistical significance attributed to sex at the significance level (0.05). in the light of the results, the researcher provided a number of recommendations. Keywords: Intermediate School Students’ Perception - Extra-Curricular Language Activities – Students’ Attitudes.